COVID-19 as a trigger for lichen planus: A case report (Indian Journal of Case Reports, 2025)
Lichen planus (LP) is an inflammatory mucocutaneous dermatosis believed to result from immune-mediated damage to basal epidermal cells, potentially triggered by an exaggerated cytotoxic T-lymphocyte response. We report the case of a middle-aged woman presenting with widespread erythematous-brown macules and papules, sparing her face and hands, which appeared 2 days after a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and were histologically diagnosed as LP. She had received three doses of the Comirnaty (Pfizer-BioNTech) coronavirus disease (COVID-19) vaccine without prior skin manifestations and had no previous COVID-19 infection. The close temporal association between SARS-CoV-2 infection and the onset of LP suggests a potential trigger. The immunological alterations associated with COVID-19, particularly immune dysregulation mediated by cytotoxic T-lymphocytes, may explain the increased propensity for LP development in such cases. Further studies involving larger populations are required to statistically validate this association.